2021
DOI: 10.3390/w13060819
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Feature Analysis for Sewer Deterioration Modeling

Abstract: Timely maintenance of sewers is essential to preventing reduced functionality and breakdown of the systems. Due to the high costs associated with inspecting a sewer system, substantial research has focused on sewer deterioration modeling and identification of the most useful features. However, there is a lack of consensus in the findings. This study investigates how the feature importance depends on the definition of bad pipes and how the feature importance changes between utilities with similar data bases. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…A wide variety of deterioration models has been developed and proposed to predict the deterioration process based on existing data and real-observed sewer conditions. Hansen et al (2021) studied a database containing 318,457 pipes from 35 utilities which are implementing deterioration models and found that the age, groundwater, and pipe shape are the most common deterioration factors used by these models. Based on Kley & Caradot (2013), these models can be categorized into three main non-exclusive groups, i.e., (i) deterministic models, (ii) statistical models, and (iii) artificial intelligence (AI) models.…”
Section: Deterioration Modelsmentioning
confidence: 99%
“…A wide variety of deterioration models has been developed and proposed to predict the deterioration process based on existing data and real-observed sewer conditions. Hansen et al (2021) studied a database containing 318,457 pipes from 35 utilities which are implementing deterioration models and found that the age, groundwater, and pipe shape are the most common deterioration factors used by these models. Based on Kley & Caradot (2013), these models can be categorized into three main non-exclusive groups, i.e., (i) deterministic models, (ii) statistical models, and (iii) artificial intelligence (AI) models.…”
Section: Deterioration Modelsmentioning
confidence: 99%
“…The inspection of the collectors is mainly done by closed circuit television video (CCTV) [4], but when the sewer is big enough to allow the access of people, this inspection is done in person [2]. Inspectors can directly observe pipeline problems, perform repairs, define maintenance works, etc.…”
Section: Introductionmentioning
confidence: 99%
“…We chose this approach because there is no comprehensive reference in the literature, and it allows us to consider failures that have the most significant impact on the asset users and lives of the residents. Imaging the underground world and understanding its condition using visual inspections and integrating this condition data in the maintenance decisions is a very popular global trend in asset management literature and practice [74,[208][209][210][211]. Despite the efforts to assess conditions of the sewer through these methods, failures caused by sinkholes seem to often catch asset managers by surprise.…”
Section: Discussionmentioning
confidence: 99%